Analisis Tingkat Pengetahuan Dukun Persalinan dalam Menolong Persalinan Menurut Standar Kesehatan dan Faktor-Faktor yang Mempengaruhinya - Nur Indah Nasution; Nadya Fitriani (STIKES Columbia Asia Medan, 2024)
This study aims to analyze the level of knowledge of birth attendants in assisting childbirth in accordance with applicable health standards, as well as identifying factors that influence the level of knowledge in Pancur Batu District, Deli Serdang Regency. The research method used was a descriptive survey with a quantitative approach, where data was collected through structured interviews and questionnaires given to 50 birth attendants in the area. Data analysis was carried out using descriptive and inferential statistical tests. The research results showed that the majority of birth attendants had low knowledge about health standards in assisting childbirth. Factors that influence this level of knowledge include age, education level, work experience, and access to health training. This research also found that birth attendants who have better access to information and training tend to have better knowledge of health standards. These findings indicate the need to improve training and education programs for birth attendants in Pancur Batu District, as well as strengthening collaboration between birth attendants and formal health workers to ensure that the delivery process is carried out in accordance with applicable health standards. This is expected to improve the quality of delivery services and reduce the risk of complications for mothers and babies.